1997
DOI: 10.1080/0141192970230405
|View full text |Cite
|
Sign up to set email alerts
|

Differential Secondary School Effectiveness: comparing the performance of different pupil groups

Abstract: This article reports the results of an Economic and Social ResearchCouncil (ESRC) funded study which focuses on the differential academic achievement of different groups of pupils. The paper describes the findings on the size and extent of school effects across 3 years (1990, 1991, 1992) for different groups of pupils (classified by gender, eligibility for free school means [FSM], ethnic group and by prior attainment). Pupils' overall General Certificate of Secondary Education performance and their performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 18 publications
3
55
0
2
Order By: Relevance
“…Some schools were markedly more effective than others in facilitating progress during the first 2 years of primary school. Finally, this study has in common with other studies (Jesson & Gray, 1991;Thomas, Sammons, Mortimore, & Smees, 1997), that it has shown that the schools were not differentially effective in the sense that the most effective schools overall were not more effective with working-class girls or pupils than other schools. Thus, even in the eight most effective schools the rate of progress made by boys was greater than the rate of progress made by the girls, and the rate of progress made by the middle-class pupils was greater than the rate of progress made by other pupils.…”
Section: Discussionmentioning
confidence: 77%
“…Some schools were markedly more effective than others in facilitating progress during the first 2 years of primary school. Finally, this study has in common with other studies (Jesson & Gray, 1991;Thomas, Sammons, Mortimore, & Smees, 1997), that it has shown that the schools were not differentially effective in the sense that the most effective schools overall were not more effective with working-class girls or pupils than other schools. Thus, even in the eight most effective schools the rate of progress made by boys was greater than the rate of progress made by the girls, and the rate of progress made by the middle-class pupils was greater than the rate of progress made by other pupils.…”
Section: Discussionmentioning
confidence: 77%
“…Evidence from research into the consistency of school effects between subjects (Luyten, 1998;Ma, 2001;Thomas, Sammons Mortimore, & Smees, 1997b) and differential school effects (Gray, Peng, Steward, & Thomas, 2004;Sammons, Nuttall, & Cuttance, 1993;Thomas, Sammons, Mortimore, & Smees, 1997a;Veenstra, 1999) shows that a general value-added indicator of school effectiveness masks all kinds of processes within the school that affect the progress of students. In an accountability system as in The Netherlands, which is based on identifying insufficient practices and schools as quickly as possible, a more sensitive system would be required in which multiple indicators of school effectiveness are simultaneously assessed, some of which are value added.…”
Section: Vmbo Tl Havomentioning
confidence: 96%
“…While it is not possible to test differential effects for all possible pupil groupings within a single model, it is important where possible to test effects in combination rather than singly, to allow for the possibility of variables being confounded (Thomas et al, 1997). The analysis presented some technical challenges.…”
Section: Differential School Effects Modellingmentioning
confidence: 99%
“…There is very little research on this phenomenon and current evidence on the existence of differential school effectiveness is mixed. Nuttall, Goldstein, Prosser and Rasbach (1989) and Thomas, Sammons, Mortimore and Smees (1997) both researching in London secondary schools report significant differential school effects in relation to prior achievement and ethnicity, with the White British -Black Caribbean gap varying significantly across schools. Smith and Tomlinson (1989) also report significant differential effects in relation to ethnicity, but conclude they are 'trivial compared with the very large school differences across all ethnic groups" (p305).…”
Section: Introductionmentioning
confidence: 99%